Effects of replacing soybean meal with linseed meal in broiler diet on selected broilers’ blood parameters, meat chemical composition, fatty acid profiles, and sensory characteristics - Tamasgen, Negasa (Frontiers in Animal Science, 2022)
The study was conducted with the objectives to determine effects of dietary replacement of soybean meal with graded levels of linseed meal on selected blood parameters, broilers meat chemical composition, fatty acids profiles and eating quality. Cobb500 broilers were fed diets containing linseed meal at 0% (T1), 6.5% (T2), 13% (T3), 19.5 (T4) and 26% (T5) replacing 0 to 100% soybean meal in compound rations for 45 days. The experiment was arranged in Completely Randomized Design with five treatments, each replicated three times with 12 birds. Blood hematology indices were not affected (P>0.05) by treatment diets while among the blood biochemistry triglyceride and Cholesterol concentration in T1 were higher (P<0.05) than T3, T4 and T5. Glucose was higher in T3, T4 and T5 than T1 and T2 (P<0.01). The breast and thigh proximate composition for CP, EE, ash, carbohydrate and gross energy were similar (P>0.05) among treatments. Sensory score for breast and thigh meat samples were not different (P>0.05) among treatments. Palmitic acid content of breast and thigh meat was higher (P<0.05) in T1 and T2 than the other treatments. Eliadic and stearic acids concentration in thigh meat were greater (P<0.05) in T1, T2 and T3 than T4 and T5. Oleic and linoleic acids content of thigh meat were higher (P<0.05) in T2 and T3 than the rest treatments. Breast linolenic acid was high (P<0.05) in T5 but similar in thigh meat. Total SFA showed a decreasing trend with increasing level of LSM in the ration. The ratio of MUFA to SFA for breast and thigh was higher in T4 and T5 than T1 and T2. Breast meat ratio of n-6 to n-3 showed a decreasing trend as the level of LSM replacement for SBM in the ration increased. Generally, linseed meal replacement up to 26% levels in broilers diet improves essential fatty acids content of chicken meat without affecting proximate composition, chickens normal blood indices and with no alteration of meat sensory attributes.